دور توجه الالكتروني في تفعيل الإدارة الإلكترونية - صفاء, بكاكرة; كنزه, طرية; محمود, حسونة (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة إلى إلقاء الضوء على الدور الذي يؤديه توجه الالكتروني في تفعيل الإدارة الإلكترونية بمديرية إدارة محلية بولاية الوادي ،من خلال تحديد تعريف توجه الالكتروني وآلياته بالاضافه الى اهم خطوات توجه الالكتروني نحو تطبيق الإدارة الإلكترونية ركز البحث على دراسه تطبيقية لمديرية الإدارة المحلية بالوادي ،قمنا فيها بتحليل الوضع الإداري والوظيفي للمديرية من أجل معرفة إلى اي مدى يساهم توجه الكتروني في تفعيل اداره للمديرية وقد أظهرت نتائج سلامة المركز الإداري في المدى القصير والطويل ،مما يدل على مساهمة توجه الالكتروني المطبق داخل مديرية إيجابيا في تطبيق الإدارة الإلكترونية""This study aimed to shed light on the role that electronic orientation harms in activating electronic administration in the Directorate of Local Administration in El Oued Province, by defining the definition of electronic orientation and its mechanisms, in addition to the most important steps of electronic orientation towards the application of electronic management. The research focused on an applied study of the Directorate of Local Administration in the Valley, in which we analyzed the administrative and functional situation of the Directorate in order to find out to what extent the electronic orientation contributes to the activation of the electronic administration of the Directorate. The results showed the safety of the administrative center of the Directorate in the short and long term, which indicates the contribution of the applied electronic orientation Within the Directorate positively in the application of electronic management. "
Keywords: التوجه الالكتروني الإدارة الإلكترونية تفعيل الإدارة الإلكترونية; electronic orientation, electronic management, activation of electronic management